Comparison of questionnaires determining patient satisfaction with medical care. - Roberts, J G (1987)
This study compares the results of previously developed patient satisfaction questionnaires which quantitatively assessed the personal attitudes of 59 patients toward their medical care. These patients, hospitalized for acute myocardial infarction, were admitted to the intensive care unit of a community hospital in southern Ontario, Canada. The questionnaires were completed by these patients at four and six months post-myocardial infarction. This quantitative assessment of patient satisfaction, as indicated by Hulka and Ware questionnaires, provided data to compare the relative effectiveness of these questionnaires in measuring satisfaction. Generally, these questionnaires were reliable (r = .64, r = .59) and evidence of criterion concurrent validity was noted (r = .75-.81). Both questionnaires have comparable results concerning the prevalence of dissatisfaction (0-7 percent).